A blast furnace gas desulfurization catalyst and desulfurization process thereof
By supporting the active components and Ag-Y molecular sieve on the γ-alumina support, the blast furnace gas desulfurization catalyst is achieved efficiently and one-step removal of organic and inorganic sulfur in the blast furnace gas, and the hydrolysis and wet methods in the prior art are solved The complexity of the desulfurization process and the problem of reducing the calorific value of the coal gas meet the industrial needs of efficient desulfurization.
Patent Information
- Application Number
- CN202211732096.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-12-30
- Publication Date
- 2025-01-07
- Estimated Expiration
- 2042-12-30
AI Technical Summary
In the existing blast furnace gas desulfurization process, the reaction of carbonyl sulfur with the alkaline sites on the surface of the catalyst during the hydrolysis process affects the conversion, and the calorific value of the gas decreases after wet desulfurization, making the process complex.
Using a blast furnace gas desulfurization catalyst, the carbonyl sulfur is converted into hydrogen sulfide by hydrolysis reaction by supporting active components and Ag-Y molecular sieve on the γ-alumina support, and hydrogen sulfide is adsorbed through the Ag-Y molecular sieve to achieve one-step decomposition Remove organic sulfur and inorganic sulfur, avoid alkali spraying and water spraying cycle washing.
The catalytic hydrolysis efficiency of carbonyl sulfur is improved, the process flow is simplified, the gas calorific value is reduced, and the blast furnace gas desulfurization is achieved, which meets industrial production requirements.
Smart Images

Figure BDA0004031928170000091
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of catalysts, in particular to a blast furnace gas desulfurization catalyst and a desulfurization process thereof. Background Art
[0002] my country is a major steel producer. In recent years, my country's steel production ranks first in the world. As an important pillar of my country's national economy, the steel industry plays a vital role in the development of all walks of life. Blast furnace gas is a by-product produced during the blast furnace ironmaking process. It is a combustible gas with the main components of 55-60% nitrogen, 6-12% carbon dioxide, 28-33% carbon monoxide, 1-4% hydrogen and a small amount of sulfide. Therefore, the exhaust gas emitted after combustion contains sulfur dioxide.
[0003] According to the "Opinions on Promoting the Implementation of Ultra-low Emissions in the Steel Industry" jointly issued by the Ministry of Ecology and Environment and other five ministries in April 2019, blast furnace gas desulfurization has become a bottleneck in the control of air pollution in the steel industry. Implementing blast furnace gas desulfurization and reducing ultra-low sulfur dioxide emissions can not only avoid the construction of decentralized end-of-pipe treatment facilities and produce significant economic and environmental benefits, but also have important significance for promoting the green development of the steel industry. Sulfides in blast furnace gas exist in the form of organic sulfur and inorganic sulfur. The content of organic sulfur is about 60-80%, of which carbonyl sulfide accounts for more than 95% of the total organic sulfur, while inorganic sulfur is mainly hydrogen sulfide.
[0004] At present, the desulfurization process of blast furnace gas is mainly divided into two steps: first, the hydrolysis method is used to remove organic sulfur with aluminum-based, titanium-based, etc. as catalysts. This step can convert most organic sulfur into chemically active hydrogen sulfide, and then the wet desulfurization method is used to remove hydrogen sulfide using alkaline solution such as sodium hydroxide. However, this process also has the following problems: First, in the hydrolysis desulfurization process, the main product of the carbonyl sulfide hydrolysis reaction is hydrogen sulfide, and blast furnace gas also contains hydrogen sulfide. When the hydrogen sulfide content increases, hydrogen sulfide will react with the alkaline sites on the catalyst surface, affecting the conversion of carbonyl sulfide. Second, when using wet desulfurization technology to treat hydrogen sulfide, since this process is a front-end treatment process, after a large amount of alkali spraying and water spraying circulation washing, the calorific value of the gas will be reduced. Therefore, it is very necessary to improve the current desulfurization process. Summary of the invention
[0005] The object of the present invention is to provide a blast furnace gas desulfurization catalyst and a desulfurization process thereof to solve the problems raised in the above background technology.
[0006] In order to solve the above technical problems, the present invention provides the following technical solutions: a blast furnace gas desulfurization catalyst and a desulfurization process thereof, comprising the following steps:
[0007] S1: After blast furnace gas is dusted, it is sent to the TRT residual pressure power generation device for gas residual pressure power generation;
[0008] S2: Dechlorination treatment is performed on the blast furnace gas after the residual pressure power generation, and then it is sent to a hydrolysis tower equipped with a blast furnace gas desulfurization catalyst for desulfurization treatment;
[0009] S3: sending the desulfurized blast furnace gas to the gas using unit; recovering and reusing the blast furnace gas desulfurization catalyst in the hydrolysis tower;
[0010] The method for preparing the blast furnace gas desulfurization catalyst comprises the following steps:
[0011] Step 1: dissolving alkali in deionized water, stirring evenly to obtain an alkaline solution, then adding an aluminum source to the alkaline solution, stirring for 30 to 60 minutes, and then adding a silicon source to obtain a mixed solution; continuously stirring and aging the mixed solution; sealing the aged mixed solution and performing hydrothermal synthesis, cooling at room temperature, centrifuging several times until the pH of the supernatant is neutral, filtering, and drying to obtain a NaY molecular sieve;
[0012] Step 2: adding NaY molecular sieve into silver nitrate solution for ion exchange, washing with deionized water, filtering, drying at 110-120° C. for 12 h, and calcining to obtain Ag-Y molecular sieve;
[0013] Step 3: using an equal volume impregnation method, the γ-alumina carrier is impregnated in the active component solution for 6 to 8 hours, dried at 120 to 140° C. for 5 to 6 hours, and calcined at 400 to 500° C. for 8 to 10 hours to obtain a γ-alumina carrier loaded with active components; using an equal volume impregnation method, the γ-alumina carrier loaded with active components is added to the promoter solution, impregnated for 6 to 8 hours, dried at 120 to 140° C. for 5 to 6 hours, and calcined at 400 to 500° C. for 8 to 10 hours to obtain modified alumina;
[0014] Step 4: The modified alumina is tableted and ground, and immersed in a 1 mol / L sodium hydroxide solution for 6 to 8 hours. After drying, the tablets are mixed with Ag-Y molecular sieves to obtain the blast furnace gas desulfurization catalyst.
[0015] Furthermore, in step 1, in the mixed solution, the molar ratio of alkali, aluminum source, silicon source and water is 6.4-8.6:1:12.6-15.4:200-235.
[0016] Furthermore, in step 1, the aging temperature of the mixed solution is 25-30° C., and the aging time is 10-12 h.
[0017] Furthermore, in step 1, the hydrothermal synthesis temperature is 75-90° C., and the synthesis time is 8-12 h.
[0018] Furthermore, in step 1, the base is any one of sodium hydroxide and potassium hydroxide.
[0019] Furthermore, in step 1, the aluminum source is any one of sodium aluminate, sodium aluminate, aluminum hydroxide, and aluminum oxide.
[0020] Furthermore, in step 1, the silicon source is any one of sodium silicate, silicate, silica sol, quartz glass, and silica gel.
[0021] Furthermore, in step 2, the specific method of the ion exchange is heating in a water bath to 70-80° C. and stirring for 24-30 hours.
[0022] Furthermore, in step 2, the amount of each component used is, by weight, 3 to 5 parts of NaY molecular sieve and 45 to 60 parts of silver nitrate solution.
[0023] Furthermore, in step 2, the concentration of the silver nitrate solution is 0.5 to 1 mol / L.
[0024] Furthermore, in step 2, the specific method of calcination is calcination at 400-500° C. for 4-6 hours.
[0025] Furthermore, in step 3, the active component is any one or more of zinc oxide, iron oxide, manganese oxide, and iron oxide.
[0026] Furthermore, in step 3, the co-catalyst is any one or more of potassium salt, calcium salt, sodium salt and magnesium salt.
[0027] Furthermore, in step 3, the contents of the components in the modified alumina are, by weight percentage, 85-90% of the γ-alumina carrier, 5-10% of the active component, and 2-5% of the promoter.
[0028] Furthermore, in step 4, the contents of the components in the blast furnace gas desulfurization catalyst are, by weight, 80 to 85 parts of modified alumina and 15 to 20 parts of Ag-Y molecular sieve.
[0029] Compared with the prior art, the beneficial effects achieved by the present invention are as follows: the present invention prepares a blast furnace gas desulfurization catalyst, wherein the active substance and the co-catalyst are loaded on a γ-alumina carrier to obtain a modified alumina, and carbonyl sulfide can be converted into hydrogen sulfide with active chemical properties through a hydrolysis reaction. Since there is also a chemical reaction between hydrogen sulfide and the active components loaded on the surface of alumina, there is a competitive relationship between hydrogen sulfide and carbonyl sulfide. By ion-exchanging the NaY molecular sieve and introducing the Ag-Y molecular sieve component with a strong adsorption effect on hydrogen sulfide, it can not only adsorb the hydrogen sulfide component originally contained in the blast furnace gas, but also adsorb the hydrogen sulfide generated in the hydrolysis reaction, thereby catalytically hydrolyzing carbonyl sulfide to a greater extent. In addition, the catalyst prepared by the present invention can remove the organic sulfur and inorganic sulfur components in a hydrolysis tower in one step, and only the catalyst needs to be recovered later, and there is no need to spray alkali and spray water for circulating washing treatment of the blast furnace gas, which is not only simple in process, but also avoids the problem of reduced calorific value of gas. DETAILED DESCRIPTION
[0030] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0031] The raw materials used in the present invention and their sources are as follows: sodium hydroxide (CAS No.: 1310-73-2), sodium aluminate (CAS No.: 11138-49-6), sodium silicate (CAS No.: 1344-09-8), silver nitrate (CAS No.: 7761-88-8), and zinc nitrate (CAS No.: 13778-38-8) were all purchased from McLean; sodium acetate (CAS No.: 6131-90-4) was purchased from Sinopharm; and γ-alumina was purchased from Zhongke Leiming Technology Co., Ltd.
[0032] Embodiment 1:
[0033] Step 1: dissolving sodium hydroxide in deionized water and stirring evenly to obtain a sodium hydroxide solution; adding sodium aluminate to the sodium hydroxide solution, stirring and aging for 30 minutes, and then adding sodium silicate to obtain a mixed solution; continuously stirring the mixed solution and aging at 25°C for 12 hours, then sealing the aged mixed solution and hydrothermally synthesizing it at 75°C for 12 hours, cooling it to room temperature, centrifuging it several times until the pH of the supernatant is neutral, filtering and drying it to obtain a NaY molecular sieve; wherein the molar ratio of sodium hydroxide, sodium aluminate, sodium silicate and water is 6.4:1:12.6:200.
[0034] Step 2: 3 g of NaY molecular sieve was added to 45 g of 0.5 mol / L silver nitrate solution for ion exchange, heated to 70°C in a water bath, stirred for 24 h, washed with deionized water, filtered, dried at 110°C for 12 h, and then calcined at 400°C for 4 h to obtain Ag-Y molecular sieve;
[0035] Step 3: using an equal volume impregnation method, the γ-alumina carrier is impregnated in a zinc nitrate solution for 6 hours, dried at 120°C for 6 hours, and calcined at 400°C for 8 hours to obtain a γ-alumina carrier loaded with zinc oxide; using an equal volume impregnation method, the γ-alumina carrier loaded with zinc oxide is added to a sodium acetate solution, impregnated for 6 hours; dried at 120°C for 5 hours and calcined at 400°C for 8 hours to obtain a modified alumina; wherein, 85% of the γ-alumina carrier, 10% of zinc oxide, and 5% of sodium oxide;
[0036] Step 4: 80 g of modified alumina was tableted, ground, and impregnated with 1 mol / L sodium hydroxide solution for 6 h. After drying, the tablet was mixed with 20 g of Ag-Y molecular sieve to obtain the blast furnace gas desulfurization catalyst.
[0037] Embodiment 2:
[0038] Step 1: dissolving sodium hydroxide in deionized water and stirring evenly to obtain a sodium hydroxide solution; adding sodium aluminate to the sodium hydroxide solution, stirring for 35 minutes, and then adding sodium silicate to obtain a mixed solution; continuously stirring the mixed solution, aging at 30°C for 12 hours, then sealing the aged mixed solution and performing hydrothermal synthesis at 80°C for 10 hours, cooling to room temperature, centrifuging several times until the pH of the supernatant is neutral, filtering, and drying to obtain a NaY molecular sieve; wherein the molar ratio of sodium hydroxide, sodium aluminate, sodium silicate, and water is 6.8:1:13.5:210.
[0039] Step 2: Add 4 g of NaY molecular sieve to 50 g of 0.7 mol / L silver nitrate solution for ion exchange, heat to 75°C in a water bath, stir for 25 h, wash with deionized water, filter, dry at 115°C for 12 h, and then calcine at 450°C for 6 h to obtain Ag-Y molecular sieve;
[0040] Step 3: using an equal volume impregnation method, the γ-alumina carrier is impregnated in a zinc nitrate solution for 7 hours, dried at 130°C for 6 hours and calcined at 450°C for 8.5 hours to obtain a γ-alumina carrier loaded with zinc oxide; using an equal volume impregnation method, the γ-alumina carrier loaded with zinc oxide is added to a sodium acetate solution, impregnated for 7 hours, dried at 130°C for 6 hours and calcined at 450°C for 8.5 hours to obtain a modified alumina; wherein, 86% of the γ-alumina carrier, 9% of zinc oxide, and 5% of sodium oxide;
[0041] Step 4: 81 g of modified alumina was tableted, ground, and impregnated with 1 mol / L sodium hydroxide solution for 7 h, and then dried and mixed with 19 g of Ag-Y molecular sieve to obtain the blast furnace gas desulfurization catalyst.
[0042] Embodiment 3:
[0043] Step 1: dissolving sodium hydroxide in deionized water and stirring evenly to obtain a sodium hydroxide solution; adding sodium aluminate to the sodium hydroxide solution, stirring for 45 minutes and then adding sodium silicate to obtain a mixed solution; continuously stirring the mixed solution, aging at 30°C for 12 hours, then sealing the aged mixed solution and performing hydrothermal synthesis at 85°C for 10 hours, cooling to room temperature and centrifuging several times until the pH of the supernatant is neutral, filtering and drying to obtain a NaY molecular sieve; wherein the molar ratio of sodium hydroxide, sodium aluminate, sodium silicate and water is 7.9:1:13.7:219.
[0044] Step 2: 3.5 g of NaY molecular sieve was added to 52 g of 0.8 mol / L silver nitrate solution for ion exchange, heated to 75°C in a water bath, stirred for 27 h, washed with deionized water, filtered, dried at 120°C for 12 h, and then calcined at 440°C for 6 h to obtain Ag-Y molecular sieve;
[0045] Step 3: using an equal volume impregnation method, the γ-alumina carrier is impregnated in a zinc nitrate solution for 7.5 hours, dried at 135°C for 6 hours and calcined at 480°C for 9 hours to obtain a γ-alumina carrier loaded with zinc oxide; using an equal volume impregnation method, the γ-alumina carrier loaded with zinc oxide is added to a sodium acetate solution, impregnated for 7.5 hours, dried at 135°C for 6 hours and calcined at 480°C for 9 hours to obtain a modified alumina; wherein, 88% of the γ-alumina carrier, 8% of zinc oxide, and 4% of sodium oxide;
[0046] Step 4: 84 g of modified alumina was tableted, ground, and impregnated with 1 mol / L sodium hydroxide solution for 6.5 h. After drying, it was mixed with 16 g of Ag-Y molecular sieve to obtain the blast furnace gas desulfurization catalyst.
[0047] Embodiment 4:
[0048] Step 1: dissolving sodium hydroxide in deionized water and stirring evenly to obtain a sodium hydroxide solution; adding sodium aluminate to the sodium hydroxide solution, stirring for 45 minutes and then adding sodium silicate to obtain a mixed solution; continuously stirring the mixed solution and aging at 25°C for 11 hours, then sealing the aged mixed solution and performing hydrothermal synthesis at 90°C for 10 hours, cooling to room temperature and centrifuging several times until the pH of the supernatant is neutral, filtering and drying to obtain a NaY molecular sieve; wherein the molar ratio of sodium hydroxide, sodium aluminate, sodium silicate and water is 7.4:1:13.8:220.
[0049] Step 2: 4.5 g of NaY molecular sieve was added to 54 g of 0.9 mol / L silver nitrate solution for ion exchange, heated to 80°C in a water bath, stirred for 27 h, washed with deionized water, filtered, dried at 115°C for 12 h, and then calcined at 420°C for 6 h to obtain Ag-Y molecular sieve;
[0050] Step 3: using an equal volume impregnation method, the γ-alumina carrier is impregnated in a zinc nitrate solution for 7.5 hours, dried at 140°C for 5.5 hours, and calcined at 460°C for 9.5 hours to obtain a γ-alumina carrier loaded with zinc oxide; using an equal volume impregnation method, the γ-alumina carrier loaded with zinc oxide is added to a sodium acetate solution, impregnated for 7.5 hours, dried at 140°C for 5.5 hours, and calcined at 460°C for 9.5 hours to obtain a modified alumina; wherein, 87% of the γ-alumina carrier, 10% of zinc oxide, and 3% of sodium oxide;
[0051] Step 4: 85 g of modified alumina was tableted, ground, and impregnated with 1 mol / L sodium hydroxide solution for 7 h, and then dried and mixed with 15 g of Ag-Y molecular sieve to obtain the blast furnace gas desulfurization catalyst.
[0052] Embodiment 5:
[0053] Step 1: dissolving sodium hydroxide in deionized water and stirring evenly to obtain a sodium hydroxide solution; adding sodium aluminate to the sodium hydroxide solution, stirring for 50 minutes and then adding sodium silicate to obtain a mixed solution; continuously stirring the mixed solution and aging it at 30°C for 11.5 hours, then sealing the aged mixed solution and performing hydrothermal synthesis at 90°C for 12 hours, cooling it to room temperature and centrifuging it several times until the pH of the supernatant is neutral, filtering and drying it to obtain a NaY molecular sieve; wherein the molar ratio of sodium hydroxide, sodium aluminate, sodium silicate and water is 8.2:1:14.8:228.
[0054] Step 2: 4.6 g of NaY molecular sieve was added to 55 g of 0.6 mol / L silver nitrate solution for ion exchange, heated to 80°C in a water bath, stirred for 30 h, washed with deionized water, filtered, dried at 120°C for 12 h, and then calcined at 400°C for 6 h to obtain Ag-Y molecular sieve;
[0055] Step 3: using an equal volume impregnation method, the γ-alumina carrier is impregnated in a zinc nitrate solution for 6.5 hours, dried at 125°C for 6 hours and calcined at 470°C for 10 hours to obtain a γ-alumina carrier loaded with zinc oxide; using an equal volume impregnation method, the γ-alumina carrier loaded with zinc oxide is added to a sodium acetate solution, impregnated for 6.5 hours, dried at 125°C for 6 hours and calcined at 470°C for 10 hours to obtain a modified alumina; wherein, 89% of the γ-alumina carrier, 9% of zinc oxide, and 2% of sodium oxide;
[0056] Step 4: 83 g of modified alumina was tableted, ground, and impregnated with 1 mol / L sodium hydroxide solution for 7 h, and then dried and mixed with 17 g of Ag-Y molecular sieve to obtain the blast furnace gas desulfurization catalyst.
[0057] Embodiment 6:
[0058] Step 1: dissolving sodium hydroxide in deionized water and stirring evenly to obtain a sodium hydroxide solution; adding sodium aluminate to the sodium hydroxide solution, stirring for 60 minutes and then adding sodium silicate to obtain a mixed solution; continuously stirring the mixed solution and aging at 30°C for 12 hours, then sealing the aged mixed solution and performing hydrothermal synthesis at 90°C for 12 hours, cooling to room temperature and centrifuging several times until the pH of the supernatant is neutral, filtering and drying to obtain a NaY molecular sieve; wherein the molar ratio of sodium hydroxide, sodium aluminate, sodium silicate and water is 8.6:1:15.4:235.
[0059] Step 2: Add 5 parts of NaY molecular sieve to 60 parts of 1 mol / L silver nitrate solution for ion exchange, heat to 80°C in a water bath, stir for 30 hours, wash with deionized water, filter, dry at 120°C for 12 hours, and then calcine at 500°C for 6 hours to obtain Ag-Y molecular sieve;
[0060] Step 3: Using an equal volume impregnation method, the γ-alumina carrier is impregnated in a zinc nitrate solution for 8 hours, dried at 140°C for 6 hours, and calcined at 500°C for 10 hours to obtain a γ-alumina carrier loaded with zinc oxide; using an equal volume impregnation method, the γ-alumina carrier loaded with zinc oxide is added to a sodium acetate solution, impregnated for 8 hours, dried at 140°C for 6 hours, and calcined at 500°C for 10 hours to obtain a modified alumina; wherein, 90% of the γ-alumina carrier, 10% of zinc oxide, and 5% of sodium oxide;
[0061] Step 4: 85 g of modified alumina was tableted, ground, and impregnated with 1 mol / L sodium hydroxide solution for 8 h. After drying, the tablet was mixed with 15 g of Ag-Y molecular sieve to obtain the blast furnace gas desulfurization catalyst.
[0062] Comparative Example 1:
[0063] No Ag-Y molecular sieve was added.
[0064] The γ-alumina carrier is impregnated in a zinc nitrate solution using an equal volume impregnation method for 6 hours, dried at 120°C for 6 hours, and calcined at 400°C for 8 hours to obtain a γ-alumina carrier loaded with zinc oxide; the γ-alumina carrier loaded with zinc oxide is added to a sodium acetate solution using an equal volume impregnation method and impregnated for 6 hours; dried at 120°C for 5 hours and calcined at 400°C for 8 hours to obtain a modified alumina; wherein, 85% of the γ-alumina carrier, 10% of zinc oxide, and 5% of sodium oxide.
[0065] Comparative Example 2:
[0066] The NaY molecular sieve was not subjected to silver ion exchange.
[0067] Step 1: dissolving sodium hydroxide in deionized water and stirring evenly to obtain a sodium hydroxide solution; adding sodium aluminate to the sodium hydroxide solution, stirring for 35 minutes, and then adding sodium silicate to obtain a mixed solution; continuously stirring the mixed solution, aging at 30°C for 12 hours, then sealing the aged mixed solution and performing hydrothermal synthesis at 80°C for 10 hours, cooling to room temperature, centrifuging several times until the pH of the supernatant is neutral, filtering, and drying to obtain a NaY molecular sieve; wherein the molar ratio of sodium hydroxide, sodium aluminate, sodium silicate, and water is 6.8:1:13.5:210.
[0068] Step 2: using an equal volume impregnation method, the γ-alumina carrier is impregnated in a zinc nitrate solution for 7 hours, dried at 130°C for 6 hours and calcined at 450°C for 8.5 hours to obtain a γ-alumina carrier loaded with zinc oxide; using an equal volume impregnation method, the γ-alumina carrier loaded with zinc oxide is added to a sodium acetate solution, impregnated for 7 hours, dried at 130°C for 6 hours and calcined at 450°C for 8.5 hours to obtain a modified alumina; wherein, 86% of the γ-alumina carrier, 9% of zinc oxide, and 5% of sodium oxide;
[0069] Step 3: 81 g of modified alumina was tableted, ground, and impregnated with 1 mol / L sodium hydroxide solution for 7 h, and then dried and mixed with 19 g of NaY molecular sieve to obtain the blast furnace gas desulfurization catalyst.
[0070] Comparative Example 3:
[0071] The Cu-Y molecular sieve was prepared by copper ion exchange on NaY molecular sieve.
[0072] Step 1: dissolving sodium hydroxide in deionized water and stirring evenly to obtain a sodium hydroxide solution; adding sodium aluminate to the sodium hydroxide solution, stirring for 45 minutes and then adding sodium silicate to obtain a mixed solution; continuously stirring the mixed solution, aging at 30°C for 12 hours, then sealing the aged mixed solution and performing hydrothermal synthesis at 85°C for 10 hours, cooling to room temperature and centrifuging several times until the pH of the supernatant is neutral, filtering and drying to obtain a NaY molecular sieve; wherein the molar ratio of sodium hydroxide, sodium aluminate, sodium silicate and water is 7.9:1:13.7:219.
[0073] Step 2: 3.5 g NaY molecular sieve was added to 52 g 0.8 mol / L copper nitrate solution for ion exchange, heated to 75°C in a water bath, stirred for 27 h, washed with deionized water, filtered, dried at 120°C for 12 h, and then calcined at 440°C for 6 h to obtain Cu-Y molecular sieve;
[0074] Step 3: using an equal volume impregnation method, the γ-alumina carrier is impregnated in a zinc nitrate solution for 7.5 hours, dried at 135°C for 6 hours and calcined at 480°C for 9 hours to obtain a γ-alumina carrier loaded with zinc oxide; using an equal volume impregnation method, the γ-alumina carrier loaded with zinc oxide is added to a sodium acetate solution, impregnated for 7.5 hours, dried at 135°C for 6 hours and calcined at 480°C for 9 hours to obtain a modified alumina; wherein, 88% of the γ-alumina carrier, 8% of zinc oxide, and 4% of sodium oxide;
[0075] Step 4: 84 g of modified alumina was tableted, ground, and impregnated with 1 mol / L sodium hydroxide solution for 6.5 h. After drying, the tablet was mixed with 16 g of Cu-Y molecular sieve to obtain the blast furnace gas desulfurization catalyst.
[0076] Comparative Example 4:
[0077] No modified alumina was added.
[0078] Step 1: dissolving sodium hydroxide in deionized water and stirring evenly to obtain a sodium hydroxide solution; adding sodium aluminate to the sodium hydroxide solution, stirring for 45 minutes, and then adding sodium silicate to obtain a mixed solution; continuously stirring the mixed solution, and aging at 25°C for 11 hours, then sealing the aged mixed solution and performing hydrothermal synthesis at 90°C for 10 hours, cooling to room temperature, centrifuging several times until the pH of the supernatant is neutral, filtering, and drying to obtain a NaY molecular sieve; wherein the molar ratio of sodium hydroxide, sodium aluminate, sodium silicate, and water is 7.4:1:13.8:220;
[0079] Step 2: Add 4.5 g of NaY molecular sieve to 54 g of 0.9 mol / L silver nitrate solution for ion exchange, heat to 80°C in a water bath, stir for 27 h, wash with deionized water, filter, dry at 115°C for 12 h, and then calcine at 420°C for 6 h to obtain Ag-Y molecular sieve as a blast furnace gas desulfurization catalyst.
[0080] Experiment: The blast furnace gas desulfurization catalysts prepared in Examples 1 to 6 and Comparative Examples 1 to 4 were loaded into a fixed bed reactor at a volume space velocity of 10 h -1 , the reaction temperature is 200℃, the reaction pressure is 0.15MPa, the gas is blast furnace gas from a steel plant, the organic sulfur is mainly carbonyl sulfide, and the inorganic sulfur is hydrogen sulfide. The experimental results are as follows:
[0081]
[0082] Conclusion: The data of Examples 1 to 6 show that the desulfurization efficiency of the blast furnace gas catalyst prepared by the present invention reaches more than 97%, has good desulfurization performance, and can meet the requirements for fine desulfurization of blast furnace gas in industrial production. Taking Example 1 as a reference, the data of Comparative Example 1 show that when the component in the catalyst is only modified alumina, carbonyl sulfide and hydrogen sulfide react with the surface active components of alumina at the same time, and the two form a competitive relationship, and the chemical properties of hydrogen sulfide are more active, so hydrogen sulfide will preferentially bind to the reaction site of the active component, affecting the conversion of carbonyl sulfide; Taking Example 2 as a reference, the data of Comparative Example 2 show that compared with Ag-Y molecular sieve, NaY molecular sieve also has an adsorption effect on hydrogen sulfide, but NaY molecular sieve has a certain hydrophilicity. In the hydrolysis tower, due to the presence of water vapor, water and hydrogen sulfide form a competitive adsorption relationship on the surface of NaY. system, so the adsorption of hydrogen sulfide by NaY molecular sieve is weakened. At the same time, in combination with Example 3 and Comparative Example 3, the adsorption of hydrogen sulfide by Cu-Y molecular sieve obtained by ion exchange with copper ions is weaker than that by Ag-Y molecular sieve, so the adsorption of hydrogen sulfide by the three is Ag-Y>Cu-Y>NaY; taking Example 4 as a reference, the data of Comparative Example 4 show that when only Ag-Y molecular sieve is used for desulfurization, the desulfurization rate is only 40.6%, which is mainly because Ag-Y has a strong adsorption for hydrogen sulfide and also has an adsorption effect on a small amount of carbonyl sulfide, but the catalytic effect mainly comes from the active components loaded on the surface of alumina.
[0083] Finally, it should be noted that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art can still modify the technical solutions described in the aforementioned embodiments or replace some of the technical features therein by equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A blast furnace gas desulfurization process, characterized in that: The following steps are involved: S1: dedusting the blast furnace gas, and then sending it to the TRT residual pressure power generation device for gas residual pressure power generation; S2: Dechlorination treatment is performed on the blast furnace gas after the residual pressure power generation, and then it is sent to a hydrolysis tower equipped with a blast furnace gas desulfurization catalyst for desulfurization treatment; S3: sending the desulfurized blast furnace gas to a gas using unit; recovering and reusing the blast furnace gas desulfurization catalyst in the hydrolysis tower; the preparation method of the blast furnace gas desulfurization catalyst comprises the following steps: Step 1: dissolving alkali in deionized water, adding an aluminum source, stirring for 30 to 60 minutes, and then adding a silicon source to obtain a mixed solution; continuously stirring and aging the mixed solution, sealing and performing hydrothermal synthesis, cooling, centrifuging, filtering, and drying to obtain a NaY molecular sieve; Step 2: adding NaY molecular sieve into silver nitrate solution for ion exchange, washing, filtering, drying and calcining to obtain Ag-Y molecular sieve; Step 3: adding the γ-alumina carrier to the active component solution by an equal volume impregnation method, drying and calcining to obtain the γ-alumina carrier loaded with the active component; adding the γ-alumina carrier loaded with the active component to the promoter solution by an equal volume impregnation method, drying and calcining to obtain modified alumina; the content of each component in the modified alumina, by weight percentage, is 85-90% of the γ-alumina carrier, 5-10% of the active component, and 2-5% of the promoter; the active component is any one or more of zinc oxide, iron oxide, and manganese oxide; the promoter is any one or more of potassium salt, calcium salt, sodium salt, and magnesium salt; Step 4: tableting and grinding the modified alumina, impregnating it with a sodium hydroxide solution for 6 to 8 hours, drying it, and mixing it with an Ag-Y molecular sieve to obtain the blast furnace gas desulfurization catalyst; the content of each component in the blast furnace gas desulfurization catalyst is, by weight, 80 to 85 parts of modified alumina and 15 to 20 parts of Ag-Y molecular sieve.
2. A blast furnace gas desulfurization process according to claim 1, characterized in that: In step 1, in the mixed solution, the molar ratio of alkali, aluminum source, silicon source and water is 6.4-8.6:1:12.6-15.4:200-235.
3. A blast furnace gas desulfurization process according to claim 1, characterized in that: In step 1, the aging temperature of the mixed solution is 25-30° C., and the aging time is 10-12 h; the hydrothermal synthesis temperature is 75-90° C., and the synthesis time is 8-12 h.
4. A blast furnace gas desulfurization process according to claim 1, characterized in that: In step 1, the alkali is any one of sodium hydroxide and potassium hydroxide; the aluminum source is any one of sodium aluminate, sodium aluminate, aluminum hydroxide, and aluminum oxide; the silicon source is any one of sodium silicate, silicate, silica sol, quartz glass, and silica gel.
5. A blast furnace gas desulfurization process according to claim 1, characterized in that: In step 2, the specific method of the ion exchange is heating in a water bath to 70-80° C. and stirring for 24-30 hours; the specific method of the calcination is calcining at 400-500° C. for 4-6 hours.
6. A blast furnace gas desulfurization process according to claim 1, characterized in that: In step 2, the content of each component is, by weight, 3 to 5 parts of NaY molecular sieve and 45 to 60 parts of silver nitrate solution.
Citation Information
Patent Citations
Fuel oil adsorption-desulfurization sorbent and preparation method thereof
CN101569853A
Desulfurizing adsorbent Ag2O / NaY based on molecular screen and preparation method thereof
CN103191697A